The role of federal transfers in regional convergence in human development indicators in Argentina - Capello, Marcelo Luis (2013)
We analyse regional convergence between Argentine provinces in well-being indicators for the period 1970-2001. More specifically, we examine the role of regional public policy in reducing the development gap between the provinces. We find strong evidence of conditional convergence in well-being indicators. However, we find no evidence that redistributive transfers from the federal government to the provinces have had a positive effect on convergence in these indicators. In fact, we find that for some schooling, health and housing measures, the effect of federal transfers on improvement rates might have been contrary to what was expected.